Synthesis, Characterization and Properties of Trimethylolpropane Triesters from Coconut (Cocos nucifera) Methyl Esters (Baghdad Science Journal, 2023)
In this study, the acid-alkaline transesterification of refined coconut seed oil (RCOSO) to fatty acid methyl ester was followed by the production of a trimethylolpropane-based thermosensitive biolubricant using potassium hydroxide, and its physicochemical characteristics were evaluated. The American Standard Test for Materials (ASTM) was employed to ascertain the biolubricant's pour point and index of viscosity, which were found to be -4 oC and 283.75, respectively. The opposite connection between lubricant viscosity and temperature was shown by the measured viscosities at varied transesterification to be transformed into biodiesel. Following this, a biolubricant was created by further transesterifiedtemperature. The ester group is verified by comparing the Fourier Transfer Infra-red (FTIR) spectra of the biodiesel and the biolubricant between absorption bands (1755.07-1737.21 cm-1). Gas chromatographic data shows that sweet almond oil contains 71.725 % unsaturated fatty acids for use as a biolubricant, 53.478 % more unsaturated fatty acids than saturated fatty acids, and 9.52 g iodine per 100 g of oil sample more than unsaturated glycerides. At 31.44 and 45.93 %, respectively, linoleic acid made up the majority among the fatty acids in the oil and synthetic biolubricant. In addition, palmitic, linoleic, and oleic acids were present in the biolubricant and coconut oil. The biolubricant's characterization results correlated highly with the ISO VG-32 standards, suggesting that it has the capacity to serve as light gear oil.